KARAKTERISTIK PENDERITA STROKE ISKEMIK ≤ 60 TAHUN YANG RAWAT INAP DI RUMAH SAKIT UMUM DELI MEDAN TAHUN 2014-2016 - Nurholijah Nasution; Sorimuda Sarumpaet; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
ABSTRACT Stroke is non communicable disease leading to emergency and body disability. According to Riskesdas 2013, North Sumatera is in the top 20 regions of high prevalence that is 10.3 per 1000 population. Prevalence of ischemic stroke is around 80-85% of all stroke cases. This research is descriptive with case series design using secondary data. Population and sample are 128 patients. Univariate data was analyzed descriptively while bivariate was analyzed by using chi-square, mann whitney and kruskall wallis tests. The result shows the highest proportion are in 56-60 years old group (48.4%), men (73.4%), Buddhism (73.4%), Tionghoa (76.6%), married (91.4%), educational status not recorded (48.4%), entrepreuner (48.4%), Medan (61.7%), limb disruption (40.6%), hypertension (53.1%), hemiparesis sinistra (48.4%), average length of stay 5 days, general cost source (79.7%), home treatment (82.0%), and Case Fatality Rate (10.2%). There is no significant difference between age group based on sex (p = 0.540) age group based on risk factor (p = 0.371), sex based on risk factor (p = 0.419), average length of stay based on age group (p = 0.145), average length of stay based on risk factor (p = 0.276), average length of stay based on paralysis location (p = 0.766), and average length of stay based on cost source (p = 0.399). Recommended to pay attention on healthy lifestyle from early age to prevent risk factors of stroke. For patients with history of hypertension to perform regular blood pressure checks and healthy lifestyle to prevent subsequent stroke. Keywords: Patient Characteristics, Ischemic Stroke, Deli Medan Hospital